Noncoding RNA Transcripts during Differentiation of Induced Pluripotent Stem Cells into Hepatocytes - Aniela Skrzypczyk; Stephanie Kehr; Ilona Krystel; Stephan H. Bernhart; Shibashish Giri; Augustinus Bader; Peter F. Stadler (Hindawi Limited, 2018)
Recent advances in the stem cell field allow to obtain many human tissues in vitro. However, hepatic differentiation of induced pluripotent stem cells (iPSCs) still remains challenging. Hepatocyte-like cells (HLCs) obtained after differentiation resemble more fetal liver hepatocytes. MicroRNAs (miRNA) play an important role in the differentiation process. Here, we analysed noncoding RNA profiles from the last stages of differentiation and compare them to hepatocytes. Our results show that HLCs maintain an epithelial character and express miRNA which can block hepatocyte maturation by inhibiting the epithelial-mesenchymal transition (EMT). Additionally, we identified differentially expressed small nucleolar RNAs (snoRNAs) and discovered novel noncoding RNA (ncRNA) genes.